Circular RNA UBAP2 (hsa_circ_0007367) Correlates with Microcirculatory Perfusion and Predicts Outcomes of Cardiogenic Shock Patients Undergoing Extracorporeal Membrane Oxygenation Support. Issue 6 (June 2022) - Li, Jiani; Yu, Zhexuan; Zeng, Jianfeng; Liu, Zhaoyuan; Zhao, Zongkai; Zhang, Yu; Li, Guanhua
ABSTRACT: Background: Severe microcirculatory disturbance is common in patients with cardiogenic shock necessitating extracorporeal membrane oxygenation (ECMO), however, biomarkers linked to microcirculation and clinical outcome are scarce. Herein we identified a circular RNA, hsa_circ_0007367, rooted from the ubiquitin-associated protein 2 ( UBAP2 ) gene, namely circUBAP2, and evaluated its biological function and the associations with microcirculation and the prognosis. Methods: Patients on ECMO with cardiogenic shock were included if qualified sublingual microcirculation parameters could be obtained and were categorized into the survivor group or non-survivor group. Macro-circulatory, microcirculatory data, cytokine levels, and relative circUBAP2 expressions were collected before, at 24 h, and at ECMO weaning off, respectively. The effects of circUBAP2 on the migration, polarization, cytokine productions, and inflammatory pathways in macrophage NR8383 cells were investigated using in vitro methods. Results: Thirty-three patients with an average age of 58.0 years were enrolled, including 19 survivors and 14 non-survivors. The survivors had higher small vessel density, perfused small vessel density (PSVD), and microvascular flow index (MFI) throughout the ECMO course than did the non-survivors. Relative expression of circUBAP2 (hsa_circ_0007367) correlated with the microcirculatory parameters and satisfactorily predicted the 30-day in-hospital mortality. A multivariable logistic model was developed, showing following four predictors: age (odds ratio [OR] 1.06, 95% confidence interval [CI] 1.00–1.12), time from shock to ECMO (OR 1.10, 95% CI 1.01–1.20), PVSD (OR 0.14, 95% CI 0.02–0.89), and the circUBAP2 expression (OR 0.25, 95% CI 0.08–0.78). In addition, circUBAP2 inhibited the migratory activity and promoted M2 polarization in macrophages, declining the productions of cytokines (tumor necrosis factor [TNF]-α, interleukin [IL]-1β, and monocyte chemotactic protein [MCP]-1) and the PI3K/Akt/mTOR pathway. Conclusion: The expression of circUBAP2 correlates with microcirculatory perfusion and has the potential in predicting outcomes for on-ECMO patients with cardiogenic shock.